Internal Models, Subordinated Debt, and Regulatory Capital Requirements for Bank Credit Risk - Kupiec, Paul. (Washington, D.C. : International Monetary Fund, 2002)
Shortcomings make credit VaR estimates an unsuitable basis for setting bank regulatory capital requirements. If, alternatively, banks are required to issue subordinated debt that has a minimum market value and maximum acceptable probability of default, banks must set their equity capital in a manner that limits both the probability of bank default and the expected loss on insured deposits, largely removing any safety net-related funding cost subsidy and the moral hazard incentives it creates. Required equity capital can be estimated using a modified credit-VaR framework, and supervisors can use external credit ratings to indirectly verify the accuracy of bank internal model estimates.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet